Sport-specific motor fitness tests in water polo: Reliability, validity and playing position differences - Uljevic, O.; Spasic, M.; Sekulic, D. (Journal of Sports Science & Medicine, 2013)
Sport-specific motor fitness tests are not often examined in water polo. In this study we examined the reliability, factorial and discriminative validity of 10 water-polo-specific motor-fitness tests, namely: three tests of in-water jumps (thrusts), two characteristic swimming sprints (10 and 20 metres from the water start), three ball-throws (shoots), one test of passing precision (accuracy), and a test of the dynamometric force produced while using the eggbeater kick. The sample of subjects consisted of 54 young male water polo players (15 to 17 years of age; 1.86 ± 0.07 m, and 83.1 ± 9.9 kg). All tests were applied over three testing trials. Reliability analyses included Cronbach Alpha coefficients (CA), inter-item- correlations (IIR) and coefficients of the variation (CV), while an analysis of variance was used to define any systematic bias between the testing trials. All tests except the test of accuracy (precision) were found to be reliable (CA ranged from 0.83 to 0.97; IIR from 0.62 to 0.91; CV from 2% to 21%); with small and irregular biases between the testing trials. Factor analysis revealed that jumping capacities as well as throwing and sprinting capacities should be observed as a relatively independent latent dimensions among young water polo players. Discriminative validity of the applied tests is partially proven since the playing positions significantly (p < 0.05) differed in some of the applied tests, with the points being superior in their fitness capacities in comparison to their teammates. This study included players from one of the world's best junior National leagues, and reported values could be used as fitness standards for such an age. Further studies are needed to examine the applicability of the proposed test procedures to older subjects and females.